Simple marketing techniques to increase sales - Khakhaieva, M. E. (ТДАТУ, 2021)
There are probably thousands of ways to boost sales and increase the inbound flow of potential customers. The problem is that there is no completely universal solution. Remember, that an idea that has worked for hundreds of companies may not work for you. You can try a lot of different marketing tactics to increase sales and only some of them will really help your company. But you should never give up, because if you look and try, you will definitely find your way.
Keywords: marketing; case marketing techniques